Attractiveness of different esthetic orthodontic wires - Deric Meschiari Batista; Melissa Faccini; Fabricio Pinelli Valarelli; Rodrigo Hermont Cançado; Renata Cristina Oliveira; Ricardo Cesar Gobbi de Oliveira; Karina Maria Salvatore Freitas (Dental Press Editora, 2021)
ABSTRACT Objective: The aim of this study was to evaluate the attractiveness of different types of esthetic orthodontic wires by laypeople and dentists. Methods: Five different types of orthodontic wires were evaluated: three esthetic wires (Teflon-coated, epoxy resin-coated and rhodium-coated wires), and two metallic wires (stainless steel and NiTi), as control. Monocrystalline ceramic brackets were installed in the maxillary arch of a patient presenting good dental alignment. The five evaluated wires were attached to the orthodontic appliance with an esthetic silicone elastic and photographed. The photographs were evaluated by 163 individuals, 110 dentists and 53 laypeople. The data were statistically evaluated by two-way ANOVA and one-way ANOVA, followed by Tukey tests. Results: There was a statistically significant difference in the attractiveness among the wires evaluated; the most esthetic was the rhodium-coated wire, followed by the epoxy resin-coated wire and, finally, the Teflon-coated wire, with no significant difference from the stainless steel and NiTi control archwires. There was no significant difference between the groups of evaluators. Conclusion: The most attractive was the rhodium-coated wire, followed by the epoxy resin-coated wire and, finally, the least attractive wire was the Teflon-coated wire, without statistically significant difference to the stainless steel and NiTi wires, used as control.